Down syndrome or Rett syndrome in the family: Parental reflections on sibling experience - Caitlin Gray; Helen Leonard; Kingsley Wong; Sally Reed; Kate Schmidt; Rachel Skoss; Jianghong Li; Alison Salt; Jenny Bourke; Emma J. Glasson (Journal of Intellectual & Developmental Disability, 2024)
Background: Siblings of children with intellectual disability have unique family experiences, varying by type of disability. Methods: Parents of children with Down syndrome (156) or with Rett syndrome (149) completed questionnaires relating to sibling advantages and disadvantages, experiences of holidays and recreation, and perceived availability of parental time. Qualitative responses were analysed using thematic analysis. Results: Positive personality traits, an optimistic outlook, enhanced skills, and rich relationships were strong and consistent parental perceptions for siblings in both disability groups. Parents of children with Rett syndrome were more likely to rank themselves lower on time availability, and to report sibling difficulties with social engagement and family holidays. Conclusions: Parental responses appeared to be influenced by disability type, and reflective of child capabilities. Perceptions of sibling experience should be supplemented by data collected directly from siblings to fully understand their unique perspective, and the ways in which their experiences could be enhanced.
Keywords: 610; siblings; intellectual disability; Down syndrome; Rett syndrome; parental reflections; family